TRANSFORMATION OF PARADIGMATIC MEASUREMENTS ON THE ESSENCE OF THE STATE AND THE CONTENT OF PUBLIC ADMINISTRATION - Solovykh V.P. (Pressing Problems of Public Administration, 2018)
Dependence of interpretation of maintenance of the state and public administration is analysed inthe article. Explored the forming stages and maintenance of such concepts as political state, legalstate and social state. Found out intercommunication of these forms of display of the state withmaintenance of public administration.